Analisis Postur Kerja Menggunakan Metode RULA dan Keluhan MSD Sopir Angkot di Tembalang - -, ekawati (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2012)
Analysis of working posture with RULA (Rapid Upper Limb Analysis) methods and Musculoskeletal Disoreder of transport driver’s in Tembalang. Musculoskeletal Disorder (MSD) is a discomfort condition on sceletal muscle, it is caused by the working exposure, unergonomic working posture. Transport driver’s is one of the workers who are at risk due to MSD because of awkward sitting work posture. The goal of this research was to describe the work postures and MSD of transport driver’s in Tembalang. The population and sample was all of transport driver’s in Tembalang. The data of work postures obtained through observation assessed using RULA methods. The data od MSD obtained through interview based on Nordic Body Map questionnaires. The result of this research showed that the work postures of transport driver’s was at action level 2 and 3; it’s mean that the next investigation was needed. All of transport driver’s had MSD condition, especially on the left leg, right leg and waist (73,3%, 63,3% dan 60%).